Two specific topoisomerase II inhibitors prevent replication of human cytomegalovirus DNA: an implied role in replication of the viral genome. - Benson, J D (1988)
In this study, we show that human cytomegalovirus DNA synthesis is inhibited in infected confluent human embryonic lung cells treated with the DNA-intercalative topoisomerase II inhibitor 4-9'-(acridinylamino)methanesulfon-m-anisidide (m-AMSA). Similar inhibitory effects were observed with VM-26, a nonintercalative topoisomerase II inhibitor. This antiviral effect is not attributable to cytotoxic effects per se. Furthermore, m-AMSA appears to have a notably irreversible inhibitory effect on human cytomegalovirus DNA replication. No inhibition of viral DNA synthesis was observed with o-AMSA, a DNA-intercalative isomer of m-AMSA that does not inhibit topoisomerase II.